2006
DOI: 10.1186/1471-2407-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Smad4-expression is decreased in breast cancer tissues: a retrospective study

Abstract: BackgroundAlthough transforming growth factor β (TGF-β) typically inhibits proliferation of epithelial cells, consistent with a tumor suppressor activity, it paradoxically also exhibits pro-metastatic activity in the later stages of carcinogenesis. Since tumors often display altered TGF-β signaling, particularly involving the Smad-pathway, we investigated the role of Smad4-expression in breast cancer.MethodsSmad4 expression was investigated by immunohistochemistry in formalin-fixed, paraffin-embedded tissue fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
7
38
0
Order By: Relevance
“…Notably, it was also demonstrated that among the 86 patients undergoing surgical resection of breast ductal carcinoma, the loss of SMAD4 expression was independently associated with poor prognosis. Patients with SMAD4-negative cancers exhibited a 2-fold greater risk of The present observation of decreased SMAD4 protein expression in breast ductal carcinoma was in agreement with the reports of Stuelten et al (37) and Ren et al (25), which also demonstrated that SMAD4 protein expression was markedly downregulated or lost in breast ductal carcinoma when compared with that in the normal breast epithelium. However, Ren et al (25) further observed that SMAD4 was highly expressed in the cytoplasm and nucleus of benign breast ductal epithelial cells, whereas it was only weakly expressed and largely restricted to the cytoplasm of cancer cells.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Notably, it was also demonstrated that among the 86 patients undergoing surgical resection of breast ductal carcinoma, the loss of SMAD4 expression was independently associated with poor prognosis. Patients with SMAD4-negative cancers exhibited a 2-fold greater risk of The present observation of decreased SMAD4 protein expression in breast ductal carcinoma was in agreement with the reports of Stuelten et al (37) and Ren et al (25), which also demonstrated that SMAD4 protein expression was markedly downregulated or lost in breast ductal carcinoma when compared with that in the normal breast epithelium. However, Ren et al (25) further observed that SMAD4 was highly expressed in the cytoplasm and nucleus of benign breast ductal epithelial cells, whereas it was only weakly expressed and largely restricted to the cytoplasm of cancer cells.…”
Section: Discussionsupporting
confidence: 82%
“…Despite one report, which demonstrated that loss of SMAD4 expression resulted in a trend for increased survival times in a subgroup of 197 cases of breast ductal carcinoma (N1 or ER-negative, respectively) (37), in the present series of 86 patients it was demonstrated that loss of SMAD4 expression was associated with increased risk of recurrence and shorter survival time. This finding corroborates the results of a study by Stuelten et al (37), which indicated that the survival curve of SMAD4-negative patients was marginally better than that of SMAD4-positive patients in terms of overall 5-year survival, although this difference was not statistically significant. These contradictory results may be due to the differences in sampling and clinical management of the disease.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Molecular detection in lung cancer also was used as predictor, such as TGF-β1, which may be an independent predictor of survival in resected lung adenocarcinoma patients [27]. SMAD4 was identified as a tumor suppressor gene and was associated with tumor invasion, metastasis and prognosis in different cancers including NSCLC [28,29]. C-Kit have critical roles in cell proliferation and differentiation in patients with NSCLC which indicate that C-Kit is a strong, independent prognostic factor in NSCLC [30].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor Smad4 acts as a central mediator of transforming growth factor b (TGF-b) signaling that plays important roles in regulating cell proliferation, differentiation, migration, apoptosis, and development (12,13). Alterations in Smad4 gene were identified in many types of cancers, including pancreatic, breast, and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%